Asymmetric Magnesium‐Catalyzed Hydroboration by Metal‐Ligand Cooperative Catalysis. (23rd October 2019) - Falconnet, Alban; Magre, Marc; Maity, Bholanath; Cavallo, Luigi; Rueping, Magnus
Abstract: Asymmetric catalysis with readily available, cheap, and non‐toxic alkaline earth metal catalysts represents a sustainable alternative to conventional synthesis methodologies. In this context, we describe the development of a first Mg II ‐catalyzed enantioselective hydroboration providing the products with excellent yields and enantioselectivities. NMR spectroscopy studies and DFT calculations provide insights into the reaction mechanism and the origin of the enantioselectivity which can be explained by a metal‐ligand cooperative catalysis pathway involving a non‐innocent ligand. Abstract : HBpin‐Aktivierung durch Mg‐Ligand‐Kooperation : Die enantioselektive, Magnesium‐katalysierte Hydroborierung von Ketonen mit einem ( R )‐(+)‐BINOL‐Derivat als chiralem Liganden liefert exzellente Ausbeuten und Enantioselektivitäten. Experimente und DFT‐Rechnungen geben Einblicke in den Reaktionsmechanismus und den Ursprung der Enantioselektivität.